Framing Banten's north coastal sea fence as eco-theology and social movement - Mukhroman, Iman; Haryanti, Erni (UIN Sunan Gunung Djati Bandung, 2025)
This study analyzes how the sea fence phenomenon on the north coast of Banten is framed differently by national online media (Republika) and local online media (Kabar Banten). Through Robert Entman's framing perspective and social movement theory, this research explores how the two media represent the phenomenon as a manifestation of social movements, religious movements, or a combination of both with eco-theological dimensions. Using a qualitative content analysis approach to 12 news articles published in January 2025, the research found significant differences in framing strategies: Republika tends to construct narratives with moral-religious and ecotheological dimensions attached to social movements, while Kabar Banten emphasizes socio-economic aspects and local community solidarity without explicit religious dimensions. These framing differences not only reflect the media's editorial orientation, but also manifest ideological contestation in representing the relationship between religion, ecology, and social movements in Indonesia. The case of the sea fence illustrates how local environmental resistance is interpreted through distinct ideological lenses, shaped by each media outlet's institutional identity and target audience. Republika’s ecotheological framing not only moralizes environmental activism through Islamic values but also seeks to legitimize community action within a broader spiritual discourse. In contrast, Kabar Banten grounds its reporting in the immediate socio-economic struggles of coastal residents, highlighting the pragmatic and communal aspects of resistance. This juxtaposition reveals the dynamic interplay between national and local narratives in constructing meaning around ecological and religious activism. Ultimately, this study contributes to an understanding of the role of media in shaping public perceptions of ecotheology-based socio-religious movements and demonstrates how media discourse influences community solidarity and environmental consciousness in the digital era.